Peran Kontrol Diri dan Gaya Hidup terhadap Perilaku Konsumtif pada Mahasiswi Selama Pandemi Pengguna Aplikasi Shopee - Rizka Ariani Nurjanah; Erita Yuliasesti Diah Sari (Empathy : Jurnal Fakultas Psikologi, 2022)
The Role of Self-Control and Lifestyle on Consumptive Behavior in College Students During a Pandemic Shopee Application Users Many people enjoy the convenience of online shopping transactions, especially during the pandemic. However, this also has negative impacts, such as wasteful behavior. This study examines the relationship between self-control and lifestyle with consumptive behavior in female students. A total of 159 female students who use the Shopee application participated in this study. Data collection uses a consumptive behavior scale, a self-control scale, and a lifestyle scale. The data analysis technique used is multiple regression analysis with the help of the SPSS program. The analysis results show a very significant relationship between self-control and lifestyle with consumptive behavior. Next, there was a very significant negative relationship between self-control and consumptive behavior. Lifestyle has a significant positive relationship with consumptive behavior. Simultaneously, self-control and lifestyle contributed 39.4% to consumptive behavior. Lifestyle contributes more to consumptive behavior than self-control. This research has implications for the need to observe a wiser and more positive lifestyle in buying behavior to reduce the tendency of wasteful behavior.